TMIC-43. ROLE OF EXTRACELLULAR FERRITIN HEAVY CHAIN PROTEIN IN GLIOBLASTOMA MULTIFORME. (11th November 2019) - Pandya, Bhavyata; Ravi, Vagisha; Connor, James
Abstract: Increased expression of Ferritin heavy chain (FHC) protein has been associated with poor prognosis in Glioblastoma Multiforme (GBM) which is one of the most aggressive and common types of brain cancer. GBM patients have also been found to have increased extracellular ferritin levels, in their serum and cerebrospinal fluid (CSF), which are lowered once the source/tumor has been resected. Extracellular FHC can function as an iron delivery protein, and increasing amount of iron has been known to contribute to tumor initiation and proliferation. To study the effect of extracellular FHC in GBM cells we used patient derived GBM, CD133+ cancer stem cells (GSCs) from the pro-neural (T3691) and mesenchymal (T387) subtypes. Using recombinant FHC, conjugated with quantum dots (QD), we observed significant increase in cellular viability and intracellular uptake of FHC by the GSCs in a dose dependent manner. Our lab has previously shown that extracellular FHC interacts with T-Cell Immunoglobulin Mucin Receptor 1 (Tim-1) in the human oligodendrocytes. In order to determine if GSCs express the Tim-1 receptor we first confirmed its expression on GSCs using immunoblotting and immunocytochemistry. To test if FHC interacts with Tim-1, we performed knockdown of Tim-1 using siRNAs. However, the siRNA was not able to downregulate the Tim-1 receptors. Next, we exposed the GSCs to Sema4A, which has been shown in our previous studies to interact with Tim-1 receptor on human oligodendrocytes and is toxic to oligodendrocytes. The GSCs however were not affected by the saturable concentration of Sema4A. Thus, through this study we have shown the expression of potential FHC receptors on GSCs and a robust effect of H-ferritin on GSCs proliferation. Further experiments are warranted in this direction to understand this extracellular FHC uptake pathway and its role in GBM cell proliferation.